Studi Evaluasi Saluran Drainase Studi Evaluasi Saluran Drainase Sebagai Upaya Penanggulangan Banjir Di Dusun Badran Asri Kabupaten Karanganyar: Saluran Drainase, Banjir, Genangan, Alternatif - Husaini, Fahri; Wijayanti, Paska; Purnomoasri, RA Dinasty (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2024)
Badran Asri Hamlet in Cangakan Village, Karanganyar District, often experiences flooding and inundation, this is due to the drainage channels being classified as poor and starting to experience a decline in the quality of the drainage channels so that they are unable to accommodate runoff water. The aim of this research is to evaluate flood management efforts and the problems that exist in the area. The method used in this research is quantitative descriptive, namely by first conducting a survey at the research location and then analyzing the data obtained. After evaluating the 10-year flood discharge of 25 channels in Badran Asri Hamlet, Cangakan Subdistrict, there were 13 channels that did not meet domestic flood discharge capacity and 12 channels that still met domestic flood discharge capacity. As an alternative, improvements need to be made by re-planning by increasing the capacity of the drainage channel in the form of a new channel as a flood management solution so that a channel discharge is obtained that is able to meet the domestic flood discharge capacity.